Paul's Python pearls - Barry, Paul, 1966- (O'Reilly Media, 2011)
"Over the past quarter century, Paul Barry has used lots of different programming languages on lots of different platforms. In this presentation, Paul discusses what it is about his current favorite language--Python--that makes it a stand-out programming technology for him. Paul discusses those Python features that are "pearls", in his opinion. You may not agree with all of Paul's picks, but we hope you'll find Paul's discussion interesting, enlightening and maybe even entertaining."--Resource description page.